2022
DOI: 10.4018/978-1-6684-2533-6.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Leadership and Well-Being in the Context of the Modern Workplace

Abstract: Organizations of modern times experience business loss in the form of financial, physical, psychological, and cultural loss with their employees, clients, suppliers, or any other related persons. To cope with such issues, we need to introduce spirituality at our workplace. and as leaders manage organizations, spiritual leadership needs immense research for growth. Spiritual leadership has been actively debated in recent decades and is a disputed subject attracting research and practice. Spirituality has evolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…They claim that a people-oriented spiritual leader can instill meaning among employees, which positively impacts the team and organization. This result is also consistent with the research of Garg, Punia, Garg, and Punia (2022), which found that employees have not only intellect but also spirit and they want to be a part of a community and see the purpose in their work.…”
Section: Discussionsupporting
confidence: 92%
“…They claim that a people-oriented spiritual leader can instill meaning among employees, which positively impacts the team and organization. This result is also consistent with the research of Garg, Punia, Garg, and Punia (2022), which found that employees have not only intellect but also spirit and they want to be a part of a community and see the purpose in their work.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the Leader-member theory of social exchange (LMX) claims that spiritual leadership impedes workers from executing UPB and unethical practices in organizational premises by sustaining them as spiritual supporters (Almutairi & Khashman, 2022). Furthermore, spiritual leaders highlight the tactics that might instigate employees to perform beyond their responsibilities and role obligations to achieve common organization and group goals (Garg, Punia, Garg, & Punia, 2022). Hence, because of such stimulation, workers sturdily identify or recognize their selves with their firms; as a consequence, their identification with organizations gets boosted (Srivastava & Madan, 2022), and as a result, the likelihood of executing UPB declines (Kelebek & Alniacik, 2022).…”
Section: Leader-member Exchange Theorymentioning
confidence: 99%
“…Centered upon the LMX theory of social exchange, in the presence of spiritual leadership, workers oversee the conduct or behavior of their spiritual leaders by seeing them as their idols and showing their behavior accordingly. Furthermore, spiritual leaders highlight the tactics that instigate employees to perform beyond their responsibilities and role obligations to achieve common organization and group goals (Garg et al, 2022). Hence, because of such stimulation, workers sturdily identify or recognize their selves with their firms; consequently, their identification with organizations gets boosted (Srivastava & Madan, 2022).…”
Section: Spiritual Leadership and Organizational Identificationmentioning
confidence: 99%